A Review of AI Image Generator: Influences, Challenges, and Future Prospects for Architectural Field - Enjellina; Eleonora Vilgia Putri Beyan; Anastasya Gisela Cinintya Rossy (Universitas Atma Jaya Yogyakarta, 2023)
Recently, the topic of text-to-image-based GAI (Generative Artificial Intelligence) or AI Image Generators became so popular because of its sophistication in creating images based on human natural language messages in a short time. On the other hand, the presence of the AI Image Generator is enough to reap various opinions, including in the field of architecture. Therefore, the purpose of this paper is to present a review of the influences, challenges, and prospects of AI Image Generator technology in the architectural design process. The research method used is a systematic literature review by reviewing 12 scientific articles, five books, and five official websites. The results of the study explained that the AI Image Generator could provide one step forward to expanding the design imagination by presenting several design alternatives with high-quality visuals. The challenge lies in the user's proficiency in providing text commands that AI programs can detect. The prospect of this program, if developed in more depth, is to become a rendering tool that can release dependence on devices with high specifications and additional editing applications.